The role of climate change in exacerbating sexual and gender-based violence in international law: In search of a solution - Moumita Mandal (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2023)
Climate change has emerged as the predominant "world problematique". Though entire populations are affected by climate change, women and girls suffer the most. The consequences of natural disasters, women face heighten real-life challenges, especially exposure to different forms of sexual and gender-based violence (SGBV). Women are exposed to SGBV due to the lack of social, economic, and political security and the culture of widespread impunity for the perpetrators. There is no specific international legal instrument that deals with SGBV against women. While scholarship outlines how climate change exacerbates SGBV against women and girls, even the texts of the three specific climate change treaties (1992 United Nations Framework Convention on Climate Change, 1997 Kyoto Protocol, and 2015 Paris Agreement) do not address the issue. Only the decisions of the Conference of the Parties in recent years have reflected the importance more recently. It is a new challenge for international law that needs to be duly addressed in a timely manner as a global common concern. Multilateralism, partnership, and cooperation at the global level could help to address the issue and find solutions. This study analyses the causal relationship between climate change and SGBV, the existing international legal instruments that are addressing the issue, and possible solutions to end SGBV.
urn:nbn:de:hbz:465-20240508-082646-0
Keywords: 320; Climate change; sexual and gender-based violence; international law; possible solutions